Femoral Venous Hemostasis in Children Using the Technique of "Figure‐of‐Eight" Sutures. (20th May 2013) - Zhou, Yong; Guo, Zhifu; Bai, Yuan; Zhao, Xianxian; Qin, Yongwen; Chen, Shaoping; Wu, Hong; Huang, Xinmiao; Li, Songhua; Liu, Bo
Abstract Background Structural heart interventions require the use of relatively large‐diameter delivery sheaths or latex nylon net balloon catheters, which results in a relatively large‐diameter venous puncture point. At present, femoral venous hemostasis is achieved by manual compression. A temporary figure‐of‐eight subcutaneous suture has been introduced to achieve immediate postprocedural femoral venous hemostasis after using a ≥24Fr sheath in an adult. This method is not well evaluated in children. Method We report our experience using this technique in children treated with 7–14Fr sheaths. From May 2009 to March 2012, 104 children (ages ranging from 3 to 10 years, mean 8.1 ± 1.6 years) with atrial septal defects (n = 86) and pulmonary valve stenosis (n = 18) underwent percutaneous transcatheter interventions. Sheath sizes used were ≥7Fr (7Fr, n = 5; 8Fr, n = 29; 9Fr, n = 14; 10Fr, n = 15; 12Fr, n = 19; 14Fr, n = 22). Result A total of 102 patients had immediate femoral vein hemostasis, and 2 developed a femoral vein hematoma requiring manual compression. One patient was diagnosed with a femoral artery pseudoaneurysm during hospitalization. On follow‐up, there was no evidence of hematoma or thrombosis. Conclusion The "figure‐of‐eight" suture technique is effective and safe, achieving immediate hemostasis after the use of large femoral vein sheaths in children.